HISTOPATHOLOGICAL STUDIES ON THE LIVER AND GILLS IN CARASSWS AVRATUS EXPOSED TO COPPER SULPHATE - Sultan, Salim; Khan, S Mahmood (Indian Journal of Fisheries, 2011)
Acute and chronic exposure to copper sulphate results in destruction ofcytoplasmic material and vacuolation of hepatocytes in Carassius auratus. Theblood sinusoids also undergo degeneration. Light microscopic studies show severehistopathological changes in gills due to exposure. Fishes exposed to chronic concentrationare more prone to disintegration